The relevance of patient‐reported outcomes in a grass pollen immunotherapy trial in children and adolescents with rhinoconjunctivitis. Issue 1 (13th August 2012) - Röder, Esther; Berger, Marjolein Y.; Hop, Wim C. J.; de Groot, Hans; Gerth van Wijk, Roy
<x xml:space="preserve">Abstract</x> To cite this article: Röder E, Berger MY, Hop WCJ, de Groot H, Gerth van Wijk R. The relevance of patient‐reported outcomes in a grass pollen immunotherapy trial in children and adolescents with rhinoconjunctivitis. Pediatr Allergy Immunol 2012. Abstract Background: Patient‐reported outcomes (PROs) are the only instruments available to assess the efficacy of an intervention in patients with allergic rhinoconjunctivitis. As allergic rhinoconjunctivitis is a systemic disease, it is now recommended to use not only PROs focusing at classical symptoms, but also health‐related quality of life (HRQL) instruments in immunotherapy trials. Methods: A previously published immunotherapy trial in children and adolescents (6–18 yr) with hay fever provided us with data to assess the relevance of two of these additional outcome measures, the disease‐specific rhinoconjunctivitis quality of life questionnaire (RQLQ) and the generic COOP/WONCA‐charts (CWC). A PRO was considered relevant if it was responsive to pollen exposure and at least had a moderate correlation with the classical symptoms of allergic rhinoconjunctivitis. Furthermore, we evaluated a post‐season PRO, that is, a global assessment of symptoms (GAS). This assessment is used in clinical trials as a tool for selecting participants with sufficient symptoms and in daily practice to evaluate the patient's complaints during the preceding season. We assessed the correlation of this retrospective score with the actual symptoms during the previous pollen season. Results: Data from 36 children and 63 adolescents were analysed. On the basis of the total scores of the paediatric and adolescent version of the RQLQ, both questionnaires were considered relevant as they were responsive to exposure and showed a moderate to strong correlation with the rhinoconjunctivitis symptoms. However, in both children and adolescents, 40% of the RQLQ items were not relevant according to our definition. The CWC as a whole and the separate charts appear less relevant because of the weak correlations with the daily symptom score from the diary. The correlation between our post‐season GAS and the in season daily symptom score was weak. Conclusion: The paediatric and adolescent RQLQ are relevant, but could be shortened as they contain a substantial number of irrelevant items. The CWC are not relevant in the monitoring of children and adolescents with allergic rhinoconjunctivitis caused by grass pollen. The retrospective GAS does not sufficiently reflect the actual symptoms during the preceding season.